POLIGAMI DALAM PERSPEKTIF ULAMA TAFSIR Catatan terhadap Pandangan Partai Solidaritas Indonesia - Baihaqi, Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2019)
Indonesia Solidarity Party (PSI), one of 2019 general election contestants, advocated poligamy refusal during its campaign. As a religion whose teachings allow poligamy, Islam is often accused by many for tolerating and legalising unfair and discriminative practices against women. This paper endeavours to offer moderate exegesis on Qur’anic verses regarding poligamy from Muslim scholars. This paper also corrects the above accusation stating that Islam is a religion practising discrimination against women. Based on descriptive literature review on the scholars’ exegesis on the Qur’anic verses on poligamy, this paper argues that to some extent, Islam permits poligamy. However, it does not encourage let alone oblige Muslim to practice poligamy. Islam requires uneasy and strict conditions for Muslim who want to practice poligamy. Partial interpretation on the verses of poligamy results in people misunderstanding of poligamy permission. Assessing Islamic teachings is only based on behaviour of some adherents who practising poligamy is not objective. This paper attempts to moderate two extreme views regarding polygamy the right one allowing poligamy practice without abiding to its rules and the left one rejecting poligamy without compromise.